The efficiency of arrest warrants issued by the ICC vis-a-vis the principle of immunity: case study of the Sudanese authorities - Sibomana, Pierre Celestin (Institute of Criminology, 2026)
Justice is a gamut that begins from the pronouncements and substance of the law to the different stages and forms of its enforcement. There are effective problems that are associated with this phenomenon. The problem of whether heads of states may be brought before courts to be criminally prosecuted is still an unsettled area of Law. This dissertation examines the efficiency of arrest warrants issued by the International Criminal Court (ICC) vis-a-vis the principle of immunity with Sudanese authorities as a case study. This problem of criminally prosecuting heads of states raises problems in international law as they normally enjoy immunity from prosecution.